(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This study employs the combined technology acceptance model (TAM) and theory of planned behavior (TPB) (i.e., C-TAM-TPB) that extended with self-efficacy and knowledge of information technology to examine HIS acceptance by Malaysian nurses. A cross-sectional survey was conducted in three public hospitals in Malaysia to gather data from practicing nurses with experience of using HIS. Structural equation modeling using the partial least squares (PLS) method was utilized to evaluate measurements and structural models. The results stress that a nurses intention was significantly influenced by three factors, including his or her attitude, the subjective norm, and perceived behavioral control. The results also indicate that the model can explain over half of the variance in the intention to use HIS.